Aung San Suu Kyi : critic or bridge builder? - Cook, Alistair David Blair (2011)
Despite the release of Aung San Suu Kyi on 13 November 2010 following the controversial national elections in Myanmar, the key challenges faced by people remain to be extreme poverty and national reconciliation. What